2019
DOI: 10.1002/hipo.23096
|View full text |Cite|
|
Sign up to set email alerts
|

NMDA receptor activity bidirectionally controls active decay of long‐term spatial memory in the dorsal hippocampus

Abstract: The time‐dependent forgetting of long‐term spatial memories involves activation of NMDA receptors (NMDARs) in the hippocampus. Here, we tested whether NMDARs regulate memory persistence bidirectionally, decreasing or increasing the rate of forgetting. We found that blocking NMDAR activation with AP5 or the GluN2B‐selective antagonist Ro25‐6981 in the dorsal hippocampus (dHPC) prevented the natural forgetting of long‐term memory for the locations of objects in an open field arena. In contrast, while enhancing N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the hippocampus, different modes of neuron oscillations occur depending on the active state. They can be divided into five categories according to different frequencies: delta oscillation (1-4Hz), theta oscillation (4-8 Hz), alpha oscillation (8)(9)(10)(11)(12)(13), beta oscillation (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma oscillation (30-80 Hz). These rhythmic oscillations of the hippocampus are closely related to the behavior and physiological state of the hippocampus, are produced by specific mechanisms, and are related to the distribution characteristics of neurons, and participate in different brain functions independently or synergistically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the hippocampus, different modes of neuron oscillations occur depending on the active state. They can be divided into five categories according to different frequencies: delta oscillation (1-4Hz), theta oscillation (4-8 Hz), alpha oscillation (8)(9)(10)(11)(12)(13), beta oscillation (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma oscillation (30-80 Hz). These rhythmic oscillations of the hippocampus are closely related to the behavior and physiological state of the hippocampus, are produced by specific mechanisms, and are related to the distribution characteristics of neurons, and participate in different brain functions independently or synergistically.…”
Section: Discussionmentioning
confidence: 99%
“…Since ketamine inhibits the neuronal activity by interfering the NMDA receptor, [2] [13] we were wondering whether interfering the NMDA receptor mediated the inhibitory effect of ketamine on hippocampal oscillation. Therefore, we added the (2R)-amino-5phosphonopentanoate (APV, 50 μM), an NMDA receptor antagonist, [14] with ketamine for bath application. We found that all the frequency bands were not affected by the ketamine with the concentration we chose (Fig.7A, B Fig.7B).…”
Section: Nmda Receptor May Be Not Essential For Ketamine Inhibiting Tmentioning
confidence: 99%
“…In their work, rats were trained in an object location task and were locally infused with different NMDAR‐blockers in the hippocampus during the retention window (up to a few days after learning). Blocking GluN2B‐NMDARs (with the antagonist Ro25‐6981) decreased forgetting as compared to controls (Migues, Wong, Lyu, & Hardt, 2019). These behavioral studies support the idea that GluN2B‐NMDARs might play a direct role in promoting forgetting.…”
Section: Proposed Molecular Mechanisms Underlying Forgettingmentioning
confidence: 98%
“…The aim of the current experiments was to determine whether reducing sensory stimulation after encoding would also enhance hippocampus-dependent memory in rats. To do this, we used a spontaneous object exploration task that assesses memory for object locations (Ennaceur and Delacour 1988;Hardt et al 2010;Migues et al 2016Migues et al , 2019. Using this approach, we replicated in rats the basic effect that quiet wakefulness promotes memory retention as previously observed in humans.…”
mentioning
confidence: 92%